Levels Of Perfluorooctane Sulfonate (Pfos) And Perfluorooctanoic Acid (Pfoa) In Home And Commercially Produced Poultry Eggs In Malaysia - Tahziz, Atiqah (2019)
Perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) are the two major perfluorinated compounds (PFCs), widely used in industrial and consumer products pertaining to their unique water and grease repellent properties. The large industrial manufacture of these compounds had raised substantial concern on health effects, due to their persistence nature and potential toxicity. The bioaccumulative properties resulted in their accumulation in environmental matrices, human samples, as well as in food sources and food products. In human, food consumption was reportedly to be a significant source of exposure for both PFOS and PFOA. Hence, the primary objective of this study was to determine the level of PFOS and PFOA in the yolk of poultry eggs in Malaysia. A total of 47 egg yolk samples, consisting of chicken eggs (n=40), duck eggs (n=3) and quail eggs (n=4) were collected from various sources of areas in Malaysia. These samples are extracted by simple protein precipitation technique using acetonitrile. The analytical method was developed using LC-MS/MS and validated based on FDA’s Bioanalytical Method Validation to ensure the quality and reliability of the method. The analysis of the samples revealed that PFOS was quantitatively detected in six samples with the concentration range between 0.5 to 1.01 ng g-1. Among these, five samples are from home produced chicken eggs, and one sample was from a quail egg.